Determination of Feeder Cell‐Based Cellular Niches Supporting the Colonization and Maintenance of Spermatogonial Stem Cells from Prepubertal Domestic Cat Testes. Issue 5 (30th June 2014) - Han, NR; Park, YH; Yun, JI; Park, HJ; Park, MH; Kim, MS; Choi, JH; Lee, E; Gong, SP; Lim, JM; Lee, ST
Contents Recently, isolation and in vitro culture of putative spermatogonial stem cells (SSCs) in the domestic cat have been conducted. However, the cellular niche conditions that facilitate the establishment and long‐term maintenance of feline SSCs (FSSCs) have not been described. Therefore, we investigated the type of feeder cells used to stimulate colony formation and growth of FSSCs among the various factors in the FSSC niche. Spermatogonial stem cells isolated from feline testes were cultured on mitotically inactivated testicular stromal cells (TSCs) derived from cats, dogs and mice, and mouse embryonic fibroblasts (MEFs). The formation and growth of colonies derived from SSCs cultured on each type of feeder cell were identified at passage 0, and the morphology, alkaline phosphatase (AP) activity and expression of SSC‐specific genes in surviving colonies were investigated at passage 4. Among these diverse feeder cells, TSCs from cat showed the greatest colony formation, growth and maintenance of FSSCs, and SSC colonies cultured by passage 4 showed a typical dome‐shaped morphology, AP activity and expression of SSC‐specific genes (NANOG, OCT4, SOX2 and CD9). Accordingly, these results demonstrate that feline TSCs could be used as feeder cells to support the establishment and maintenance of SSCs from domestic cats.